2016
DOI: 10.1111/evo.13090
|View full text |Cite
|
Sign up to set email alerts
|

Tempo does not correlate with mode in the fossil record

Abstract: The dominating view of evolution based on the fossil record is that established species remain more or less unaltered during their existence. Substantial evolution is on the other hand routinely reported for contemporary populations, and most quantitative traits show high potential for evolution. These contrasting observations on long- and short-time scales are often referred to as the paradox of stasis, which rests on the fundamental assumption that periods of morphological stasis in the fossil record represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 91 publications
(206 reference statements)
2
43
4
Order By: Relevance
“…Time series of phyletic evolution in the fossil record represent important data for understanding evolutionary change spanning more than a few decades. Comparing how alternative models fit fossil time series has greatly increased our ability to understand evolution on macroevolutionary time‐scales (e.g., Hopkins & Lidgard, ; Hunt, , ; Voje, ), but Akaike information criteria and likelihood ratio tests cannot evaluate the adequacy of fit between the model and data. Investigating the relative and absolute fit of Hunt's () models stasis, random walk and directional change to 300 fossil time series showed that most of the analysed data on phyletic evolution in the fossil record are adequately described by one of the three models (73%), but more than a quarter is not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Time series of phyletic evolution in the fossil record represent important data for understanding evolutionary change spanning more than a few decades. Comparing how alternative models fit fossil time series has greatly increased our ability to understand evolution on macroevolutionary time‐scales (e.g., Hopkins & Lidgard, ; Hunt, , ; Voje, ), but Akaike information criteria and likelihood ratio tests cannot evaluate the adequacy of fit between the model and data. Investigating the relative and absolute fit of Hunt's () models stasis, random walk and directional change to 300 fossil time series showed that most of the analysed data on phyletic evolution in the fossil record are adequately described by one of the three models (73%), but more than a quarter is not.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the data analysed in this study overlap with the data analysed in Voje et al. (), Voje (), Hunt (), Hopkins and Lidgard () and Hunt et al. (), but were filtered to meet certain criteria: Each time series had to consist of at least 10 sample means and time had to be on an absolute scale (in stead of relative).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They argue that "the remarkable stasis exhibited by most species during millions of years is ignored (as no data)" (Gould & Eldredge, 1993). Indeed, studies on patterns of change in the fossil record have confirmed that stasis is a far more common observation than phyletic gradualism (Hunt, , 2007Hunt & Rabosky, 2014), with stasis, in this sense, more accurately regarded as directionless or nonaccumulating morphological fluctuations rather than true stagnance (Gould, 1982;Gould, 2002;Voje, 2016). The assumption that discontinuities are artifacts of incompleteness implies that phyletic gradualism is synonymous with evolution.…”
Section: Punctuated Equilibriummentioning
confidence: 99%
“…The problem of evolutionary stasis has been discussed at depth in the evolutionary literature (Merilä et al. ; Hansen and Houle ; Voje ). Here, we show using combination of field studies and phylogenetic comparative analyses that several of the proposed mechanisms that could generate stasis are unlikely to explain slow body size evolution in odonates.…”
mentioning
confidence: 99%